Adaptive Distributed Cooperative Tracking Control and Application for Multiagent Formation Under Communication Constraints - Zhang, Jialong; Ye, Lei; Hou, Zhongxi; Yu, Li; Cai, Jia (IEEE transactions on aerospace and electronic systems, 2024)
This article studies the problem of distributed adaptive cooperative tracking for multiagent systems with communication constraints in complex communication environments. For this problem, a novel quantitative adaptive tracking control strategy is proposed based on adaptive backstepping technology, quantization theory, and variable transformation. First, the mechanism of communication between agents or between agents and ground stations is analyzed and quantized. And a multiagent swarm formation model with quantized inputs is established by considering a class of high-order nonlinear multiagent systems with partially unknown parameters. Moreover, the limitation of the nonholonomic constraint is removed via the variable transformation method. The adaptive backstepping method is used to design an adaptive cooperative tracking controller to update the unknown parameters of the model in real-time. Formation flight is maintained by designing time-varying reference trajectories to track the desired specified positions. Then, the rationality of the proposed method is verified in terms of Lyapunov stability. Finally, the designed control strategy is applied to a scaled-down model for an unmanned aerial vehicle formation to further verify its effectiveness in practical engineering applications.